Cooperative design, visualization, and engineering : 16th International Conference, CDVE 2019, Mallorca, Spain, October 6-9, 2019 : proceedings /: 16th International Conference, CDVE 2019, Mallorca, Spain, October 6-9, 2019 : proceedings. ([2019]) - Unknown
No abstract available